Resilient City: A Bibliometric Analysis and Visualization - Qiaoyun Yang; Dan Yang; Peng Li; Shilu Liang; Zhenghu Zhang (Discrete Dynamics in Nature and Society)
Resilient city has attracted global attentions as a new concept for cities to deal with risks and challenges in recent years. Numerous researchers have successively conducted in-depth studies on the resilient city from different perspectives. To acquire an overview of resilient city and grasp the current research hotspots, a bibliometric analysis and visualization of the past decade of research on the resilient city was made. The data were collected from 1249 articles published in the Web of Science database from 2010 to 2019. As the widely used bibliometric analysis tools, CiteSpace and VOSviewer were adopted in this study. The temporal distribution of resilient city research, including annual publication outputs and high-cited papers, was symmetrically analyzed. Then, the spatial distribution of resilient city research, including countries, categories, institutions, co-citation journals, author collaboration network, and author co-citation network, was investigated. Hot topics and evolution trends of resilient city were revealed. The results show that the research of resilient city experienced three periods, namely, germination, rapid diffusion, and reflection and innovation periods. Current research focuses on four aspects, including psychological resilience at the microcommunity and group levels, assessment of urban disaster resilience, multiple theoretical frameworks of urban resilience, and urban resilience promotion strategy. Therefore, this study helps scholars and practitioners to gain a comprehensive understanding of the current research progress and evolution trends of the resilient city field.